High-performance sport governance, funding, and talent development in developed and developing countries: a systematic review - Juliana Sattu; Fadli Ihsan; Eval Edmizal (Lentera Negeri, 2026)
High-performance sport management is central to a nation’s success in international competitions. Developed countries have long established integrated, evidence-based systems for elite sport development, while developing nations often face fragmented structures, weak governance, and limited resources. This systematic review analyzes and compares high-performance sport management models in developed and developing contexts, highlighting structural, policy, and outcome differences. Using PRISMA guidelines, 22 peer-reviewed studies published between 2013 and 2023 from Scopus, Web of Science, and SPORTDiscus were examined. A comparative framework guided thematic analysis, focusing on governance, funding, talent identification, infrastructure, coaching, and sport science integration. Findings reveal that developed nations implement centralized, data-driven models underpinned by long-term funding, robust governance, and strong institutional alignment. These elements enable sustainable elite sport systems. In contrast, developing countries often adopt ad hoc strategies, lack policy continuity, and struggle with limited access to sport science and infrastructure. Replicating developed-country models without contextual adaptation frequently results in inefficiency. The study concludes that effective high-performance sport management requires systemic coherence, strategic investment, and context-sensitive adaptation. Rather than imitation, developing nations should integrate key principles into resilient and locally grounded frameworks. By employing SPLISS, RBV, and Institutional Theory, this review contributes to advancing global sport policy discourse.